Using buildings' foundation as a GHE in moderate climates - Aresti, Lazaros; Christodoulides, Paul; Florides, Georgios A. (My University, 2020)
Shallow Geothermal Energy, a Renewable Energy Source, finds application through Ground Source Heat Pumps (GSHPs) for space heating/cooling via tubes directed into the ground. There are two main categories of Ground Heat Exchanger (GHE) types: the horizontal and the vertical types. Ground Heat Exchangers (GHEs) of various configurations, extract or reject heat into the ground. Even though GSHP have higher performance in comparison to the Air Source Heat Pumps (ASHPs), the systems high initial costs and long payback period have made it unattractive as an investment. GSHP systems can also be utilized in the buildings foundation in the form of Thermo-Active Structure (TAS) systems or Energy Geo-Structures (EGS), with applications such as energy piles, barrette piles, diaphragm walls, shallow foundations, retaining walls, embankments, and tunnel linings. Energy piles are reinforced concrete foundations with geothermal pipes, whereby the buildings foundations are utilized to provide space heating and cooling. Apart from energy piles, another EGS system can be achieved by the incorporation of the building’s foundation bed as a GHE. Foundation piles are not required in all constructions, but a building’s foundation bed is mandatory. This configuration is still based on the principles of the energy pile.